IMPLEMENTASI KEBIJAKAN KARTU JAKARTA SEHAT (KJS) DI DKI JAKARTA - Yessica .; Turtiantoro .; Achmad Taufiq (Journal of Politic and Government Studies, 2014)
Health is one of the primary needs for everyone so the need for health insurance. Health insurance basically aims to provide health services to the community because in reality many of the limitations of the poor to meet the primary needs that the government also intervened in this matter, as stipulated in Law No. 36 of 2009 Number of health states that the government is responsible for the willingness access to information, eduksi, and health care facilities for the community. So the Jakarta administration to make a health policy based on Jakarta Governor Decree No. 187 of 2012 About Acquisition Cost of Health Care named Jakarta Health Cards "KJS".  Policy of Jakarta Healthy Card or "KJS" is a guarantee of health care for the poor residents of Jakarta and vulnerable to the residence for a minimum of three (3) years, with the aim of improving public health Jakarta optimally and comprehensively. Based on Jakarta Governor Regulation No. 14 Year 2013 on Amendment to Regulation No. 187 of 2012 Governor On Acquisition Costs of Health Services.This study aims to analyze policy implementation Jakarta Health Card and see the factors inhibiting and supporting policies that affect the success of Jakarta Health Card (KJS). As for analyzes using indicators proposed by Van Meter and Van Horn. To obtain the research data and events using descriptive qualitative method.Where all actors implementing examined using interviews. The conclusions of this study are as follows. When described as a whole then the conclusion is not yet achieved the goal to maximum KJS. Some of the factors that affect the function and role of health centers and hospitals that do not comply with the part that is dealing KJS to the public, causing a buildup of KJS cards at health centers and resulted in many people who do not get a card with KJS and related facilities and infrastructure. Although the government continues to increase the facilities, in fact there are still many patients who have to wait to get a third class room in the hospital so the health care received by patients experiencing delays. This study took the scope of work in the area of Jakarta Provincial Government. Phenomenon and the data successfully identified and collected in this study, arranged to get a picture of implementation of policy Jakarta Health Card (KJS) within the scope and focus of the analysis.